Effect of Food and Esomeprazole on the Pharmacokinetics of Alectinib, a Highly Selective ALK Inhibitor, in Healthy Subjects. Issue 4 (28th September 2016) - Morcos, Peter N.; Guerini, Elena; Parrott, Neil; Dall, Georgina; Blotner, Steven; Bogman, Katrijn; Sturm, Carolina; Balas, Bogdana; Martin‐Facklam, Meret; Phipps, Alex
Abstract: Alectinib, an anaplastic lymphoma kinase (ALK) inhibitor, is approved for treatment of patients with ALK + non–small cell lung cancer who have progressed, on or are intolerant to, crizotinib. This study assessed the effect of a high‐fat meal and the proton pump inhibitor, esomeprazole, on the pharmacokinetics (PK) of alectinib. This was an open‐label, 2‐group study in healthy subjects. In group 1 (n = 18), subjects were randomly assigned to a 2‐treatment (A, fasted conditions; B, following a high‐fat meal), 2‐sequence (AB or BA) crossover assessment, separated by a 10‐day washout. In group 2 (n = 24), subjects were enrolled in a 2‐period, fixed‐sequence crossover assessment to evaluate the effect of esomeprazole. PK parameters were evaluated for alectinib, its major similarly active metabolite, M4, and the combined exposure of alectinib and M4. Administration of alectinib following a high‐fat meal substantially increased the combined exposure of alectinib and M4 to 331% (90%CI, 279%–393%) and 311% (90%CI, 273%–355%) for Cmax and AUC0–∞, respectively, versus fasted conditions. Coadministration of esomeprazole had no clinically relevant effect on the combined exposure of alectinib and M4. Alectinib should be administered under fed conditions to maximize its bioavailability, whereas no restrictions are required with antisecretory agents.